A paisagem no ensino de Geografia: reflexões a partir da abordagem de professores e livros didáticos de ensino médio - Freire, Laurecy Rodrigues (Universidade Federal do Tocantins, 2018)
The present work consists of a study about the landscape in the teaching of Geography, whose general objective is to analyze how the concept of landscape by teachers and Didactic Book in High School in the public schools of Porto Nacional - TO is approached. In order to reach the general objective, a bibliographical survey was carried out concerning the concept of landscape in geographic science and the concept of landscape present in the didactic book adopted by the schools studied was also investigated. In order to do so, we analyzed 7 didactic collections of High School, each collection has 03 volumes. The Guide of the PNLD 2015 Textbook was used because it is the guiding guide for the analyzed collections that belong to the triennium 2015, 2016 and 2017. For this analysis was taken into consideration: landscape conception - to observe how the author understands this concept (the elements that consider members of the landscape) to verify if the landscape appears as a specific content (unit of the book) or is recurrent throughout the didactic book; to observe if there is any suggestion of practical activity in relation to the concept of landscape; as the author of the book suggests working with this concept, as well as with the bibliographical suggestion. It was also analyzed the methods adopted by the teachers to work the landscape in High School and its relation with the Didactic Book. We interviewed 7 teachers of Geography of the state public schools that offer High School in the municipality of Porto Nacional - TO. It was possible to verify that the concept of landscape is mentioned in the books from the concept of geographic space, being little worked in the didactic collections in general. Based on the interviews, it was found that teachers understand the importance of the concept of landscape for the development of students and seek to approach this concept from the student's daily life, thus enhancing their prior knowledge. The teachers stated that despite the difficulties encountered to perform the practical classes, it is necessary to create viable alternatives so that the process of teaching learning occurs in a significant way.